The The Activity Test of Laban Bark Infusion (Vitex Pubescens Vahl) In Mice (Mus Musculus) As Antidiarrheal (INTEGRATION PROCEEDING, 2023)
Diarrhea is an endemic disease and also a potentially becomes Incident Outside Normal (ION). ION itself explained as emergence or increasing incident pain and or meaningful death in an epidemiology manner of area in a period certain time, and is a possible situation that lead to plague occurrence. An acute diarrhea could result in fatal events up to death if not handled fast. The use of traditional drug culture in Indonesia itself has also increased every year along with the thinking pattern of society that want to return to nature (back to nature). Traditional drug plant alone is still easily found in nature, one example the plant is laban plant (Vitex pubescens V.) The purpose of this study was to determine if there is an activity in laban bark as an antidiarrheal. The method used was a quantitative experimental with true experimental design study pretest and posttest control group design. Samples were mice in one negative control group (blank), two positive control groups (Loperamide HCl and New Diatabs), and three Laban Bark Infusion (LBI) groups (LBI 13,2 [g] LBI 26,4 [g], and LBI 52,8 [g]). Analyzed with Kruskal – Wallis test with a 95 [%] confidence level. The results of this study were that the most significant found in the LBI 52,8 [g] group. Based on the results of the conclusion that there is an activity in Laban Bark Infusion as an antidiarrheal.